NALISIS PEMBAYARAN GAJI DAN UPAH PADA PT WAHAU HARAPAN MANDIRI DI SANGATTA - -, Hamidah - (EKONOMIA, 2014)
The purpose of this study was to determine the payment of salaries and wages in PT Wahau Harapan Mandiri in sangatta and determines the suitability of the payment of salaries and wages by East Kalimantan Governor regulation No. 561 / K.806 / 2013 of the provincial minimum wage. Research carried out for 3 months (April to June 2014) at PT. Wahau Harapan Mandiri in sangatta, relating to the payment of salaries and wages. Research activities are : Literature study, field observation, interview, Documentation, Data Collection and Analysis.Data collected in the study include: an overview of the company, organization structure and respondents. Analysis tool used is comparison that compares the salaries and wages applied by PT. Wahau Harapan Mandiri, with salaries and wages by East Kalimantan Governor Decree No. 561 / K.806 / 2013 concerning the determination of the minimum wage.The results of the analysis mentioned wages applied in PT. Wahau Harapan Mandiri are appropriate withÂ Governor of East Kalimantan Regulation on the Minimum Wage Standard (UMP) Rp. 1,956,535. Moreover the minimum wage based on the number of operators working hours Rp. 2,000,000 net of taxes, especially income tax article 21